Business as usual ; Feisty Shay Cullen ; Ibang iba ang lasa [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Examines the effects of the seventh coup attempt on business and the economy. An Irish priest in Olongapo City faces hostile townfolk who want him out of the country, for his call for social reforms and strong objections to the presence of the U.S. bases. The Champoy gang of Noel Trinidad and Subas Herrero are back on the air after four years.